Arte clásico y arte moderno como influencia en las prácticas artísticas actuales. - Espinoza Romero, Juan Carlos (2015)
This paper emphasizes the research d descriptive representation of classical art and modern art and its influence on current artistic practices . Work that took place in the city of Machala El Oro province .